Assessing Religious Obligations: A Phenomenological Approach to Value and Legal Perspectives - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2024)
This research begins an effort to overcome the complex challenges of formulating the concept of religious obligations among diverse Indonesian society. This study emphasizes the importance of understanding aspects of these obligations in the context of Indonesia's national ideology, Pancasila, which emphasizes the principle of Belief in One Almighty God. Facing the legal and ethical complexities involved, this research uses a juridical-normative approach as an analytical framework to examine and understand policies surrounding religious obligations in Indonesia. The juridical-normative approach is very useful in identifying and interpreting government policies and societal norms that influence religious adherence in a country. Although the Indonesian government does not strictly require its citizens to adhere to only officially recognized religions — namely Islam, Christianity, Hinduism, and Buddhism — there is a fundamental tension between formal recognition and actual practice. The research results show that in practice, adherents of local beliefs such as Sundanese Wiwitan, Kaharingan, and Parmalim, which are inherited from generation to generation, often face discrimination that is contrary to the spirit of the first principle of Pancasila. This research illustrates the tension between official lists of religions and the reality that not all spiritual denominations are treated equally. This gap between policy and practice raises questions about the consistent application of Indonesia's constitutional law and the basic ideology of Pancasila across the diverse religious spectrum. This study aims to be a first step to further explore and discuss the complexity of religious obligations and freedom in Indonesia, especially in the context of the legal and ethical framework.